Evidence of genetic structure in a wide‐ranging and highly mobile soaring scavenger, the Andean condor. Issue 11 (13th June 2018) - Padró, Julian; Lambertucci, Sergio A.; Perrig, Paula L.; Pauli, Jonathan N.
Abstract: Aim: Evaluating the patterns of genetic variation and population connectivity is fundamental to effectively designing and implementing conservation strategies for threatened species. However, connectivity patterns in highly mobile vertebrates, and especially in avian species, are often overlooked as it is generally assumed to be driven by demographic panmixia or isolation by distance. Herein, we investigated the genetic structure and patterns of connectivity across four biomes in a highly vagile bird, the Andean condor ( Vultur gryphus ). Location: Four major Neotropical biomes of Argentina (>300, 000 km 2 ): Puna, Monte, Chaco and Patagonia. Methods: We genotyped 13 polymorphic microsatellite loci plus one sex‐determining gene in 300 moulted feathers from 13 roosting sites in the core of species distributional range. We quantified levels of genetic differentiation, population structure, effective gene flow, genetic diversity and assessed sex‐biased dispersal events. Results: We detected genetic structure with a moderate differentiation between the north (Puna and Chaco) and south (Patagonia) regions with a contact zone in the central area (Monte). We observed a spatial pattern of genetic patches with higher levels of gene flow along the Andes range. Although we found no indication of bottlenecks or inbreeding, we observed larger effective population sizes in the south compared to the northern region. Main conclusions: Our study revealed that, despite the high dispersal potential of condors, demographic panmixia is not consolidated, even in the core of this species range. Our analyses further suggest that gene flow rate is modulated by topographic features, as condors may disperse more following the natural updrafts and lifts along the Andean mountains. Conservation initiatives should prioritize the protection of the Andean corridor to maintain connectivity between the apparent source from Patagonia to the northern biomes.